2003
DOI: 10.1093/ps/82.6.1030
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary fructooligosaccharide on digestive enzyme activities, intestinal microflora and morphology of male broilers

Abstract: Two hundred forty male Avian Farms broiler chicks, 1 d of age, were randomly allocated to four treatments, each of which had five pens of 12 chicks per pen. The chicks were used to investigate the effects of fructooligosaccharide (FOS) on digestive enzyme activities and intestinal microflora and morphology. The chicks received the same basal diet based on corn-soybean meal, and FOS was added to the basal diet at 0, 2.0, 4.0, and 8.0 g/kg diet at the expense of corn. Addition of 4.0 g/kg FOS to the basal diet s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

30
431
2
20

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 712 publications
(511 citation statements)
references
References 14 publications
30
431
2
20
Order By: Relevance
“…The results of improvement of the intestinal integrity observed in the present study were reflected in the performance results, since according to XU et al (2003) clay possess the capacity to absorb and excrete pathogenic microorganisms present in the poultry's gastrointestinal tract which promotes improvements in the environment and in the epithelium and, consequently, greater use of nutrients.…”
Section: ----------------------------------------------------------(3supporting
confidence: 56%
See 1 more Smart Citation
“…The results of improvement of the intestinal integrity observed in the present study were reflected in the performance results, since according to XU et al (2003) clay possess the capacity to absorb and excrete pathogenic microorganisms present in the poultry's gastrointestinal tract which promotes improvements in the environment and in the epithelium and, consequently, greater use of nutrients.…”
Section: ----------------------------------------------------------(3supporting
confidence: 56%
“…According to MACARI et al (2002), the absorptive capacity of the intestine will be directly proportional to the size of the villi and poultry with higher villi may have a better absorption of nutrients. The intake of clays can improve the intestinal integrity through its role in absorption and excretion of pathogenic microorganisms in poultry gastrointestinal tract (XU et al, 2003). HU et al (2013) observed improvements in intestinal integrity measured by the villi height by providing clay (montmorillonite) to broiler chickens.…”
Section: ----------------------------------------------------------(3mentioning
confidence: 99%
“…The underlying mechanism is related to the fact that increased villus height and villus height-to-crypt depth ratio are directly correlated with an increased epithelial turnover (Sinol et al 2012), and longer villi are linked with activation of cell mitosis (Samanya and Yamauchi 2002). Shortening of villi and deeper crypts lead to poor nutrient absorption, increased secretion in gastrointestinal tract and reduced performance (Xu et al 2003). Intestinal morphology including duodenal and ileal villus height and crypt depth and villus height-to-crypt depth ratio are indicative In the current study, the inclusion of tri-strain probiotics increased relative weight bursa to the BW compared to the control group.…”
Section: Discussionmentioning
confidence: 99%
“…Prebiotics have been used in nutrition research with canines (Verlinden et al, 2006;Apanavicius et al, 2007), felines (Hesta et al, 2005), poultry (Xu et al, 2003), swine (Yasuda et al, 2007), horses (Bailey et al, 2007), young ruminants (Kaufhold et al, 2000;Heinrichs et al, 2003) and adult ruminants (Franklin et al, 2005). Although some prebiotics such as scFOS, OF, inulin, mannanoligosaccharides (MOS) and galactooligosaccharides have been supplemented to cows (Mwenya et al, 2005), calves (Masanetz et al, 2011) and lambs (Thayne, 2007) and some information is available on the effects of feeding prebiotics in selected species mentioned above (Swanson et al, 2002a), there is no information on the effects of supplemental inulin in kids.…”
Section: Introductionmentioning
confidence: 99%